Aspectos anatomopatológicos, imuno-histoquímicos e moleculares da infecção por herpervírus humano tipo 1 em primatas neotropicais - Pavelegini, Lucas Avelino Dandolini (2022)
This work describes the anatomopathological, molecular and immunohistochemical findings of an outbreak of mortality of black-tailed marmoset (Mico melanurus) and Night-Monkey (Aotus azarae) due infecction by Human Herpesvirus type 1 that occuredin a park in the municipality of Cuiabá, Mato Grosso. Between October and November 2020 the Zoonosis Surveillance Unit (UVZ) of Cuiabá-MT sent to HOVETUFMT - Cuiabá, 14 neotropical primates from a yellow fever suspected epizootic. ThreeMico melanurus sent alive with neurological alterations were clinically evaluated and subsequently euthanized in extremis. During the necropsy of the 14 neotropical primates, the most common macroscopic findings were lingual ulcers and brain hyperemia. Microscopically, the main lesion consisted of acute multifocal necrotic and non-purulent meningoencephalitis with intranuclear eosinophilic inclusion body. The polymerasechainreaction (PCR) detected viral DNA in 7/9 oftheevaluated cases. Immunohistochemistry (IHC) showed a positive result in 11/13 ofthe cases.